Transversus thoracis muscle plane block in cardiac surgery: a pilot feasibility study. Issue 5 (21st March 2019) - Fujii, Satoru; Roche, Matthew; Jones, Philip M; Vissa, Deepti; Bainbridge, Daniel; Zhou, Jian Ray
Abstract : Introduction: Cardiac surgery patients often experience significant pain after median sternotomy. The transversus thoracis muscle plane (TTP) block is a newly developed, single-shot nerve block technique that provides analgesia for the anterior chest wall. In this double-blind pilot study, we assessed the feasibility of performing this novel block as an analgesic adjunct. Methods: All patients aged 18–90 undergoing elective cardiac surgery were randomized to the block or standard care control group on admission to the intensive care unit after surgery. Under ultrasound guidance, patients in the block group received the TTP block with 20 mL of either 0.3% or 0.5% ropivacaine bilaterally, based on weight. The control group did not receive any injections. All blocks were performed by a single anesthesiologist, and data collection was performed by blinded assessors. The primary feasibility outcomes were rate of recruitment, adherence, and adverse events. The rate of recruitment was defined as the ratio of patients giving informed consent to the number of eligible patients who were approached to participate. Secondary outcomes included 12-hour and 24-hour Numeric Rating Scale (NRS) pain scores, 24-hour hydromorphone and acetaminophen requirements, time to extubation, time to first opioid administration, and patient satisfaction (on a yes/no questionnaire) at 24 hours. Results: Twenty patients were approached for this study and 19 were enrolled. Eight patients received the intended intervention in each group. The recruitment rate was 95% of all approached eligible patients, and the adherence rate to treatment group was 94%. There were no block-related adverse events. The mean (SD) NRS pain scores at rest were 3.3 (3.2) in the block group vs 5.6 (3.2) in the control group at 12 hours. At 24 hours, the pain scores were 4.1 (3.9) vs 4.1 (3.3) in the block and control group, respectively. The mean (SD) 24-hour hydromorphone administration was 1.9 (1.1) mg in the block group vs 1.8 (0.9) mg in the control group. Discussion: The TTP block is a novel pain management strategy poststernotomy. The results reveal a high patient recruitment, adherence, and satisfaction rate, and provide some preliminary data supporting safety. Trial registration number: NCT03128346 .